Особливості діагностики оптичних характеристик монокристалів синтетичних алмазів, вирощених методом температурного градієнта для створення еталонів теплопровідності - Івахненко, С.О.; Гонтар, О.Г.; Занєвський, О.О.; Ткач, В.М.; Куцай, О.М.; Івакін, Є.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
It has been shown that usually if the syntetic diamond grown on seed crystal in the Fe-Ni
system it can demonstrate different yellow coloration. Typically the yellow diamond crystals have distorted cuboctahedral shape. The colourless was distributed as cubic areas and rather irregular patches in yellow crystal. Usually in yellow diamond the colourless area is related with nitrogen centеrs. It is characteristic for the mixed Ia+Ib type syntetic diamond crystals. But for some crystals it was discovered absence of absorption in one area. It means that concentration of nitrogen less 1 ppm. It is characteristic for the crystals of the mixed type Ib+IIa . It has been shown how useful this growing technicue for studying of the syntetic diamond optical properties.